THE LOGIC OF ACCOUNTS. - Littleton, A. C. (The Accounting Review, 1955)
This article says that an American, E.G. Folsom, made a praiseworthy attempt two generations ago to show the student that bookkeeping procedures reflect rational purposes and implement reasonable and understandable objectives. His pedagogical intention dearly was one of easing the learner's task by teaching him the thought processes behind the technical features of double entry. In this approach he displays a penetrating insight into the weakness of learning a technology by memorizing rules for dealing with typical situations. Perhaps Folsom was Conditioned by his education to attempt the broadening of instruction in bookkeeping. He signed his book as a master of arts and displays an acquaintance with the economics of his day far beyond that reflected in most contemporary text books on bookkeeping. One of Folsom's aims in writing his text, like that of many other authors, was to teach the student how to analyze transactions into debits and credits for entry into double entry ledger accounts.